August folly - Thirkell, Angela, 1890-1961 (Virago modern classics., 2014)
It's August in the Barsetshire village of Worsted, and Richard Tebben, just down from Oxford, is contemplating the gloomy prospect of a long summer in the parental home. But the numerous and impossibly glamorous Dean family--exquisite Rachel, her capable husband and six of their nine brilliant children--have come for the holidays, and their hostess Mrs Palmer plans to rope everyone into performing in her disastrous annual play. Surrounded by the irrepressible Deans, Richard and his sister Margaret cannot help but have their minds broadened, spirits raised and hearts smitten.